2019
DOI: 10.3390/ijms20205086
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of the Extracellular Matrix Signature in Macrophages of Different Activation Status: Relevance for Skin Wound Healing

Abstract: The extracellular matrix (ECM) provides structural support for tissue architecture and is a major effector of cell behavior during skin repair and inflammation. Macrophages are involved in all stages of skin repair but only limited knowledge exists about macrophage-specific expression and regulation of ECM components. In this study, we used transcriptome profiling and bioinformatic analysis to define the unique expression of ECM-associated genes in cultured macrophages. Characterization of the matrisome reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 92 publications
(98 reference statements)
1
46
0
Order By: Relevance
“…Transforming growth factor beta-induced protein (TGFBI, also known as βig-H3 and keratoepithelin) is an extracellular matrix molecule secreted by many cell types including keratinocytes [ 29 , 30 , 31 ] that regulates keratinocyte function [ 30 ], plays a critical role in extracellular matrix interactions [ 32 ], could increase adhesion, migration and proliferation of epithelial cells [ 33 ], could impair the function of fibroblasts in chronic wounds [ 34 ] and is therefore supposed to play an essential role in skin wound healing [ 34 , 35 , 36 ]. According to the whole transcriptome analyses gene expression of TGFBI was approx.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor beta-induced protein (TGFBI, also known as βig-H3 and keratoepithelin) is an extracellular matrix molecule secreted by many cell types including keratinocytes [ 29 , 30 , 31 ] that regulates keratinocyte function [ 30 ], plays a critical role in extracellular matrix interactions [ 32 ], could increase adhesion, migration and proliferation of epithelial cells [ 33 ], could impair the function of fibroblasts in chronic wounds [ 34 ] and is therefore supposed to play an essential role in skin wound healing [ 34 , 35 , 36 ]. According to the whole transcriptome analyses gene expression of TGFBI was approx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our co-localization studies demonstrated for the first time that EMILIN-3 was not only expressed by odontoblasts, but that the protein was also found in CD68 and HLA-DR positive cells. A role of EMILIN-3 in immunity has not yet been investigated, however, a recent gene expression study reported EMILIN-1 and EMILIN-2 as two of the most highly expressed glycoproteins in human macrophages during wound healing 50 . A previous study had already shown that EMILIN-1 and EMILIN-2 are strongly upregulated in the wound bed 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Dermal macrophages express CD163 and factor XIIIa (Valladeau et al, 2000;Nestle et al, 2009). Dermal macrophages also promote the proliferation of fibroblasts in damaged tissue to assist with repair in a TGFα, fibroblast growth factor (FGF), and platelet-derived growth-factor-dependent mechanism (Shook et al, 2018;Etich et al, 2019).…”
Section: Skinmentioning
confidence: 99%
“…LCs coordinate a state of immune tolerance in the postnatal skin but can instruct the adaptive immune system when skin integrity is compromised (Seneschal et al, 2012). During the early stages of wound healing, LCs are present as an immune barrier and coordinate with dermal macrophages to promote repair in a fibroblast-dependent manner (Shook et al, 2018;Etich et al, 2019). Little is known about the function of LCs during development, but data suggests they could be involved in ECM remodeling alongside dermal macrophages (Furio et al, 2010).…”
Section: Skinmentioning
confidence: 99%